2019
DOI: 10.1038/s41598-019-56365-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of T Follicular Helper Cells and T Follicular Regulatory Cells in the Pathogenesis of Autoimmune Hemolytic Anemia

Abstract: Autoimmune hemolytic anemia (AIHA) is an acquired autoimmune disease mediated by antibodies against the patient’s red blood cells. However, the underlying mechanisms for antibody production are not fully understood. Previous studies of etiology and pathogenesis of AIHA mainly focus on autoreactive B cells that have escaped tolerance mechanisms. Few studies have reported the function of TFH and TFR cells in the process of AIHA. The present study aimed to explore the potential mechanism of TFH and TFR cells in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…It was demonstrated that the immune dysregulation present in AIHA may be associated with specific cytokine gene polymorphisms, which may then result in a Th17/Tregs imbalance [41][42][43]. Recent research into the AIHA mouse model has demonstrated the role of T follicular helper cells (Tfh) and T follicular regulatory cells (Tfr) in participating in B cell differentiation and regulation of anti-RBC antibody production [44]. The results of a recent study revealed that AIHA is also associated with the presence of clonal expansions of CD8+ T cells, yet the immune clones persisted during remission of AIHA and did not correlate with disease severity, duration, nor hemoglobin level, and were probably induced and accumulated during the autoimmune process [45].…”
Section: Pathogenesis Of Aihamentioning
confidence: 99%
“…It was demonstrated that the immune dysregulation present in AIHA may be associated with specific cytokine gene polymorphisms, which may then result in a Th17/Tregs imbalance [41][42][43]. Recent research into the AIHA mouse model has demonstrated the role of T follicular helper cells (Tfh) and T follicular regulatory cells (Tfr) in participating in B cell differentiation and regulation of anti-RBC antibody production [44]. The results of a recent study revealed that AIHA is also associated with the presence of clonal expansions of CD8+ T cells, yet the immune clones persisted during remission of AIHA and did not correlate with disease severity, duration, nor hemoglobin level, and were probably induced and accumulated during the autoimmune process [45].…”
Section: Pathogenesis Of Aihamentioning
confidence: 99%
“…Thus, a lower MCHC and higher Ret suggest that patients with primary w-AIHA may have a higher risk of early recurrence. As an autoimmune disease, it is expected that immune cells play an important role in the pathogenesis and progression of AIHA (32,33). However, early clinical works did not pay sufficient attention to immunologically relevant indicators, such as absolute counts of lymphocyte subpopulations and serum immune factor levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-five mice were selected and randomly divided into normal control group, model group. We established AIHA mouse models using classical rat erythrocyte intraperitoneal immunization [ 20 , 21 ]. After adaptive feeding for one-week, healthy female C57BL/6J mice (age, 6–8 weeks; weight, 20–25 g) were weighed, then blood was collected from the inner canthus.…”
Section: Methodsmentioning
confidence: 99%